Factors Affecting Attitude Toward Private Labels: A Pilot Study Between Turkey And Germany - (:unkn) unknown (INT MANAGEMENT DEVELOPMENT ASSOC-IMDA, 2012)
Private label (PL) is one of the tools used by retailers to increase market share, penetration, store loyally, human traffic, frequency of purchase. PL has gained significant importance in all over the world. Like global retailers, national and local retailers in Turkey and Germany also give increasingly more spaces in their shelves and stores for their own Private Labels. The aim of this study is to specify the factors affecting the attitudes of the Turkish and German consumers toward Private Labels. Findings of this study may shed light on retailers and manufacturers in developing their PL strategies.
Keywords: STORE BRANDS; ANTECEDENTS; PRODUCTS; PURCHASE; LOYALTY; IMAGE